Analisis Manajemen Risiko Berbasis ISO 31000 pada Usaha Jasa Fotografi: Studi Kasus Kara Project - Salsha Dwi Agustien; Rahma Khairunnisa Amalia; Maisya Hayina Zahra Zahra; Ghina Aulia Asy-syifa; Alfiana Alfiana (Indo Publishing, 2026)
This study analyzes risk management based on ISO 31000 in Kara Project, an individually operated photography service. Photography work depends heavily on equipment reliability, digital data security, workflow accuracy, and direct interaction with clients, making the business vulnerable to various operational and reputational risks. Using a descriptive qualitative approach, data were collected through field observations and interviews with the owner to obtain a comprehensive understanding of risks encountered in daily activities. The findings reveal fifty-seven distinct risks that span across equipment performance, client coordination, financial processes, scheduling, and the personal workload inherent in single-operator businesses. The ISO 31000 framework provides a structured basis for organizing these risks, supporting more informed decision-making, and enhancing overall service consistency.